A System for Harvesting Eggs from the Pink-Spotted Lady Beetle - Margaret L. Allen; Eric W. Riddick (Psyche: A Journal of Entomology)
We describe a system for harvesting eggs from a predatory insect, the pink-spotted lady beetle, Coleomegilla maculata De Geer (Coleoptera: Coccinellidae). Adult beetles placed in square, transparent containers that included oviposition substrates hanging from the top of the cage deposited eggs on the materials provided. We harvested eggs from these substrates in quantities sufficient for either destructive sampling or synchronous development of larvae. We evaluated effects of crowding inside cages; effects of a chemical attractant on oviposition behavior; egg cannibalism. Females preferred a textured surface rather than a smooth, waxy one for laying eggs. Crowding inhibited oviposition of beetles. Presence of a chemical attractant (methyl salicylate) did not significantly improve oviposition. This paper describes an inexpensive system for harvesting eggs from C. maculata. Refinement of this system should improve oviposition and reduce cannibalism.